Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus dan Dana Bagi Hasil Terhadap Belanja Modal - Faisal, Yusuf; Yanti, Lupita Putri; Novelita (Jurnal Samudra Ekonomika, 2024)
This study aims to determine the effect of Local own-source revenue, General allocation funds, Special allocation funds and Revenue share funds on Capital expenditures. This research uses quantitative data, the sample in this study is 8 districts and 1 city of Bali Province. The data source used is the annual report for the 2015-2020 period. The analysis technique used to test the hypothesis is multiple regression analysis using E-views 9 software. The results of this study indicate that the Local own-source revenue variable has a positive and statistically significant effect on Capital expenditures, the General allocation funds variable has a negative and statistically insignificant effect on Capital Expenditures, the Special allocation funds variable has a positive and statistically insignificant effect on Capital expenditures, and the Revenue share funds variable has a negative effect and is statistically not significant on Capital expenditures.This study discusses Capital expenditures and other factors such as Local own-source revenue, General allocation funds, Special allocation funds and Revenue share funds which focus on Regency/City of Bali Province.